Twin Follicular Cysts in a Crossbred Cow: a Case Report - S. Satheshkumar; A. Ganesan; Chhavi Gupta; M. Murugan; J. Jayalakshmi; A. Palanisammi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Follicular cyst is an important ovarian dysfunction and a major cause of reproductive failure in dairy cattle which has an economic impact on dairy industry. With the advent of imaging diagnostics follicular cyst has been defined as follicle like structures, with a minimum diameter of 17 mm and persisting for more than 6 days in the absence of a corpus luteum (Silvia et al., 2002). Calder et al. (2001) has explained the different natures of follicular cysts in cattle. This paper places on record the co-existence of two types of follicular cysts and therapeutic approach in a crossbred cow.